Preoperative Albumin–Bilirubin Grade With Prognostic Nutritional Index Predicts the Outcome of Patients With Early-Stage Hepatocellular Carcinoma After Percutaneous Radiofrequency Ablation - Pan, Jingying; Chen, Shuochun; Tian, Guo; Jiang, Tianan (Frontiers in Medicine, 2020)
Background: Prognostic nutritional index (PNI) that was designed to assess the nutritional and immunological status of patients and albumin–bilirubin (ALBI) grades can be used as an assessment tool for hepatic function. Both nutritional and immunological statuses have been reported to be independent prognostic factors of patients with hepatocellular carcinoma (HCC). This study aimed to investigate whether PNI together with ALBI could be a better predictor in patients with early-stage HCC undergoing radiofrequency ablation (RFA). Method: The information of 110 patients with newly diagnosed HCC within the Milan criteria receiving RFA as the initial therapy between 2014 and 2015 was retrospectively collected. Pretreatment PNI, ALBI, and PNI-ALBI grades were calculated. Overall survival (OS) and recurrence-free survival (RFS) were estimated by the Kaplan–Meier method, and multivariate analysis was used to identify prognostic factors. Result: The 1-, 3-, and 5-years OS rates of patients were 80.0, 30.9, and 23.9%, respectively. Multivariate analysis showed that the tumor size [hazard ratio (HR) = 1.966, 95% confidence interval (CI) = 1.091–3.545, P = 0.025], PNI grade (H = 2.558, 95% CI = 1.289–5.078, P = 0.007), and PNI-ALBI grade (HR = 3.876, 95% CI = 1.729–8.690, P = 0.001) were independent risk factors for OS, whereas only the elevated α-fetoprotein (HR = 1.732, 95% CI = 1.003–2.991, P = 0.049) and the size of the tumor (HR = 1.640, 95% CI = 1.015–2.647, P = 0.43) were independent predictors for better RFS. Conclusion: This study demonstrates that preoperative PNI-ALBI grade is a simple and useful predictor for OS in patients with early-stage HCC after RFA.